2012
DOI: 10.1200/jco.2012.30.15_suppl.6630
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary safety and efficacy of ruxolitinib in patients (pts) with primary and secondary myelofibrosis (MF) with platelet counts (PC) of 50–100x109/L.

Abstract: 6630 Background: Ruxolitinib (RUX) has demonstrated clinical benefit as therapy for MF. This study explores the safety and efficacy of RUX in pts with MF and low PC, where clinical data are limited. Methods: In this phase II study, pts with intermediate-1 to high-risk MF, and PC of 50–100x109/L started RUX at 5 mg BID. Doses could be increased in 5 mg QD increments every 4 weeks (wks) beginning at wk 4. Doses were decreased or held for PC <35x109/L and <25x109/L respectively. Assessments: Total Symptom … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Alternate dosing strategies are currently being investigated in MF patients with platelet counts between 50–100 x 10 9 /L in a phase II, open label trial of 24 weeks duration. 34 The starting dose is 5 mgs twice daily, and dose optimization may occur on a 4-weekly basis dependent on toxicity. Interim analysis (n = 41) has shown that only 4 patients required dose interruption due to a fall in platelet count to <25 x 10 9 /L.…”
Section: Clinical Studies and Efficacymentioning
confidence: 99%
“…Alternate dosing strategies are currently being investigated in MF patients with platelet counts between 50–100 x 10 9 /L in a phase II, open label trial of 24 weeks duration. 34 The starting dose is 5 mgs twice daily, and dose optimization may occur on a 4-weekly basis dependent on toxicity. Interim analysis (n = 41) has shown that only 4 patients required dose interruption due to a fall in platelet count to <25 x 10 9 /L.…”
Section: Clinical Studies and Efficacymentioning
confidence: 99%